Hak Ulayat sebagai Manifestasi Maqāṣid al-Sharī‘ah dalam Pengelolaan Sumber Daya Alam: Analisis Kasus Masyarakat Adat Dayak Kenyah di Kalimantan Timur - Surono, Agus; Wenceslaus, Wenceslaus (STAINI Press, 2025)
This research departs from the paradox between the state's normative recognition of the rights of indigenous peoples and the reality of structural marginalization experienced by the Dayak Kenyah community in Pampang Village, East Kalimantan. Customary rights as a system of communal ownership have not only legal value, but also spiritual and ecological dimensions that are in line with the principles of maqāṣid al-sharī'ah, in particular ḥifẓ al-māl (protection of property) and ḥifẓ al-bi'ah (protection of the environment). This study uses a normative legal approach supported by qualitative case studies to analyze the relationship between customary law, national law, and Islamic law in natural resource governance. Data was collected through analysis of laws and regulations, court decisions, and interviews with traditional stakeholders. The results of the study show that there is an overlap of sectoral regulations, complicated bureaucracy for verification of customary rights, and the dominance of state economic interests that get rid of customary authorities. The analysis of maqāṣid al-sharī'ah shows that the recognition of customary rights is a tangible manifestation of social justice and ecological responsibility mandated by Islamic law. Therefore, strengthening customary institutions, harmonizing sectoral regulations, and implementing the principle of Free, Prior, and Informed Consent (FPIC) are strategic steps towards fair, sustainable, and maqāṣid governance.